EVALUASI KAPASITAS DAN KESELAMATAN LALU LINTAS AKIBAT PENGEMBANGAN INFRASTRUKTUR PELABUHAN MALOY - ikbal, Muhammad Ikbal; santo, Susanto; fikar, Mhd. Alfikar Marpaung (Yayasan Nusantara Hasana Berdikari, 2025)
This study evaluates the impact of the Maloy Port development on traffic performance along the Maloy Port Access National Road using Traffic Impact Analysis (Andalalin). Increased logistics activity and heavy-vehicle intensity raised traffic volume by 25–30 percent and reduced the Level of Service (LOS) from category B to C. Nevertheless, the roadway remains within a safe operating condition, indicated by an average degree of saturation (DS) of 0.09, following the MKJI (1997) standard. The research employs a descriptive qualitative approach through field observations, interviews, and technical document review to assess changes in traffic flow characteristics, capacity, and conflict points in the port area. The findings identify four major conflict points, with the highest risk occurring along the heavy-vehicle exit route. Technical interventions—including temporary one-way flow management, shoulder widening, and improvements to signage and pavement marking—enhanced traffic efficiency by up to 22 percent. These results underscore the need to integrate Andalalin recommendations with sustainable transportation principles and the potential application of Intelligent Transportation Systems (ITS) for real-time traffic management. The study contributes theoretically to the understanding of the interrelationship between port development, roadway capacity, and traffic safety, and provides practical guidance for evidence-based and adaptive traffic management policies.